거세불안의 표상에 관한 연구 - 김인숙; In Sook Kim (기초조형학연구, 2016)
세기말 백인남성주체의 위기를 시사하는 시대상의 반영으로서 프로이드의 거세 불안은 초기에는 성적 욕망의 좌절이라는 관점에서 이해되지만 라캉에 의해 거세공포는 성적 담론의 범주를 넘어 욕망에 토대를 둔 인간 주체의 보편적 불안으로 확장되면서 그 내용으로서 동일시와 결핍, 환상 등이 분석된다. 이와 같은 라캉의 도식은 로라 멀비의 페미니즘과 호미 바바의 탈 식민 이론에 수용됨과 동시에 포스트모던 미술의 시각언어로도 전화(轉化)된다. 결과적으로 거세공포는 이미지의 시각언어에 대한 이해의 영역을 확장하면서 동시대 미술의 다양한 이미지 생산은 물론 기존의 미술사 또한 새로운 시선으로 재해석되고 있다. 이에 본고에서는 기존의 미술사에서는 영세하게 다루거나 거의 언급되지 않았던 거세 불안을 이론적 배경으로 하여 피카소의 < 아비뇽의 아가씨들 >, 마르셀 뒤샹의 < 에땅 도네 >, 신디 셔먼의 < 무제 #258 >, 모리무라 야스마사의 < 이중신분 >을 재해석하고자 한다. 이와 같은 시도는 미술사의 영역에 갇혀 오독(誤讀)되거나 박제화 되고 있는 작품들 사이의 유기적 맥락을 환기함과 아울러 이와 같은 논의가 오늘 우리의 분열된 주체의 이해에도 연계되어 있음을 밝힘으로써 작품의 감상과 제작에 새로운 관점을 제시할 수 있을 것으로 기대한다. Castration complex``, as a reflection of the times explaining a crisis of apocalyptic caucasian male subjects, could be initially understood in a perspective of frustration of sexual desire. However, castration complex started to expand to humanly common anxiety structured for identification, desire and fantasy beyond the category of sexual discussion by Lacan and ,as being accepted to feminism and post-colonial theory, was transformed to visual language of post modern art with such theoretical backgrounds. As this kind of accomplishment expands a visual language of image about an area of understanding, not only various image production of contemporary art but also existing art history were being reinterpreted in a new perspective. Even though these arts were not treated in the identical context, this paper is to extend the range of interpretation through Picasso``s < Les Moiselles d``Avignon >, Duchamp``s < Etant Donne >, Sherman``s < Untitled film still #258 >, Morimura``s < Dual Identity > with identical discussion of castration complex. This kind of trial is expected to ventilate the organic context between arts which could be wrongly interpreted or stuffed by being locked in an area of art history. Furthermore it is expected to suggest a new perspective to appreciation and production of the art by clarifying that this kind of discussion is also connected to understanding of our separated subjectivity.